2017
DOI: 10.1177/0021955x17720156
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polymer foam anisotropy on energy absorption during combined shear-compression loading

Abstract: Polymeric foams are extensively used in applications such as packaging, sports goods and sandwich structures. Since in-service loading conditions are often multi-axial, characterisation of foams under multi-axial loading is essential. In this article, quasi-static combined shear-compression behaviour of isotropic expanded polystyrene foam and anisotropic polyethersulfone foam was studied. For this, a testing apparatus which can apply combined compression and transverse shear loads was developed. The results re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…The combined shear‐compression set‐up comprises of two independent displacement actuators which apply simultaneous shear and compressive displacements in two orthogonal axes resulting in combined shear and compressive loading of the foam specimens. This set‐up was extensively described in our previous paper . The biaxial shear‐compression tests are performed at deformation angle of 45° meaning that both shear and compressive displacement rates were set at 2 mm min −1 .…”
Section: Methodsmentioning
confidence: 99%
“…The combined shear‐compression set‐up comprises of two independent displacement actuators which apply simultaneous shear and compressive displacements in two orthogonal axes resulting in combined shear and compressive loading of the foam specimens. This set‐up was extensively described in our previous paper . The biaxial shear‐compression tests are performed at deformation angle of 45° meaning that both shear and compressive displacement rates were set at 2 mm min −1 .…”
Section: Methodsmentioning
confidence: 99%
“…A limitation of the present FE model is the modelling of the shear behaviour of the foam core. Mosleh et al [8] concluded that characterisation of cellular materials under multi-axial loading is necessary for the use of realistic and complex failure criteria in structural design, taking into account multiple loading directions. Lei et al [29] found that the shear modulus of the foam was also al.…”
Section: Results Of Hexapod Impact Tests On Kevlar-rohacell Sandwich mentioning
confidence: 99%
“…Instead, the structures are more frequently loaded at some oblique angle or complex trajectory such as collision with floating or submerged objects and low-speed berthing impacts [6] or lateral collisions in bridge [7]. The investigation of behaviour of sandwich composite to dynamic multi-axial loading is of great importance as in-service loading conditions are often multi-axial due to the complex geometries of structures and intricate loading conditions [8].…”
Section: Introductionmentioning
confidence: 99%
“…water blown free rise polyurethane foams) can have highly anisotropic void shapes. The ellipsoidal shape of the voids formed during foaming has been found to greatly influence the material's stiffness during various loading types like tensile [34,35], compression [36,37], and impact loading [38]. With respect to mode I fracture, the influence of void anisotropy has been investigated for ductile materials [39] and cases where the crack tip is located in the void, for infinite materials [40].…”
Section: Effects Of Manufacturing Inaccuracies On the Stress Intensitmentioning
confidence: 99%